Synthesis and Effect of the Structure of Bithienyl-Terminated Surfactants for Dielectric Layer Modification in Organic Transistor - Lucia Feriancová (MDPI AG, 2021)
A series of bithienyl-terminated surfactants with various alkyl chain lengths (from C8 to C13) and phosphono or chlorodimethylsilyl anchoring groups were synthesized by palladium-catalyzed hydrophosphonation, or platinum-catalyzed hydrosilylation as a key step. Surfactants were tested in pentacene or α-sexithiophene-based organic field-effect transistors (OFETs) for the modification of the dielectric surface. The studied surfactants increased the effective mobility of the α-sexithiophene-based device by up to one order of magnitude. The length of alkyl chain showed to be significant for the pentacene-based device, as the effective mobility only increased in the case of dielectric modification with bithienylundecylphosphonic acid. AFM allowed a better understanding of the morphology of semiconductors on bare SiO2 and surfaces treated with bithienylundecylphosphonic acid.